A pull-through operation for perirectal venous malformation - Hira Ahmad; Samuel Hwang; Vijay Shah; Richard J. Wood; Giridhar M. Shivaram; Caitlin A. Smith (Elsevier, 2021)
Venous malformations (VM) of the pelvis are rare and difficult to treat due to extensive lesional feeding vessels. Little exists in the published literature for management of such conditions in children, but lessons learned from congenital causes can help. Herein we discuss the preoperative evaluation and management of an 11-year-old child with a congenital pelvic and perirectal VM that presented as hematochezia. MRI showed extensive malformation with involvement of the calf, leg, perirectal region, and pelvis. The patient had continued hematochezia despite several sclerotherapy and embolization attempts. She eventually underwent transanal and open Swenson type pull-through and resection of colonic and rectal VM with derotation of the transverse colon, and has been doing extremely well since her operation.